Tournament Incentives Affect Perceived Stress and Hormonal Stress Responses - Thomas Dohmen; Ingrid M.T. Rohde; Tom Stolp (Institute of Labor Economics (IZA), 2023)
We conduct a laboratory experiment among male participants to investigate whether rewarding schemes that depend on work performance – in particular, tournament incentives – induce more stress than schemes that are independent of performance - fixed payment scheme. Stress is measured over the entire course of the experiment at both the hormonal and psychological level. Hormonal stress responses are captured by measuring salivary cortisol levels. Psychological stress responses are measured by self-reported feelings of stress and primary appraisals. We find that tournament incentives induce a stress response whereas a fixed payment does not induce stress. This stress response does not differ significantly across situations in which winners and losers of the tournament are publically announced and situations in which this information remains private. Biological and psychological stress measures are positively correlated, i.e. increased levels of cortisol are associated with stronger feelings of stress. Nevertheless, neither perceived psychological stress nor elevated cortisol levels in a previous tournament predict a subsequent choice between tournaments and fixed payment schemes, indicating that stress induced by incentives schemes is not a relevant criterion for sorting decisions in our experiment. Finally, we find that cortisol levels are severely elevated at the beginning of the experiment, suggesting that participants experience stress in anticipation of the experiment per se, potentially due to uncertainties associated with the unknown lab situation. We call this the novelty effect.
Keywords: D23; D87; D91; M52; 330; incentives; stress; cortisol; sorting; laboratory experiment